Kajian Desain Perhiasan Tulola Jewelry Dengan Inspirasi Budaya Bali - Rika Nugraha (JURNAL RUPA, 2016)
The potential of jewelry Indonesia in the international high-end segment is Tulola Jewelry that resemble the culture of the archipelago through the inspiration of Balinese culture , thus successfully penetrate the world market .The purpose of this paper is first, Tulola jewelry to produce products worldwide . Secondly, Tulola jewelry inspired by the culture of Bali. Third, how to design visualization of Tulola Jewelry The method used is the qualitative approach to the study of iconography as identification, description and interpretation of icons based on the attributes of the marker .The end result of this research collaboration Tulola Jewelry is a traditional Indonesian jewelry with a modern twist , excellence Tulola Design Jewelry as jewelry Indonesia has a distinctive feature compared with jewelry from other countries . A blend of modern technology and traditional Balinese motifs make jewelry look artistic .